Development of Intelligent Distributed Temperature Monitoring System - Ahmed Ali, Abduasslam (2001)
Distributed sensors could be used in a temperature monitoring system to track the change in temperature in a laboratory or any other room. The temperature monitoring system can be made intelligent by integrating it with a dialing system that warns against the unwanted temperatures that exceed some predefined limits. Such a system could be utilized in places where the temperature plays an important role. Tissue Culture laboratory is one of the laboratories that could get advantage of this system. Tissue culture laboratory has a large number of tissue samples of various plants. Those tissue samples have to be kept in a specific range of temperature. Researchers need to maintain the temperature within the limits by adjusting the air conditioner to the required temperature. However, there might be a failure in the air conditioner due to lack of gas or thermostat malfunctioning. Temperature in that case will rise or drop and goes beyond the wanted limits. This problem might happen in the working time hours or off time when nobody is around to notice the change in temperature. Accordingly, a need of a remote alarm system is of great importance to warn the related person for the situation. This thesis deals with this problem and provides a system that monitor the temperature of the rooms and make emergency call to a pre-programmed number in case of temperature rise or drop out of a predefined range. Development of this system is divided into two main tasks. The first task is to develop a system that reads the temperature of the rooms and passes it to the microcontroller's analog to digital inputs. Then, it displays the temperatures on a computer's monitor. The second task is to develop a dialing system that dials a specified number in case the temperature exceeds limits of 29°C to 31 0c. Motorola MC68HCl1 is programmed to monitor the temperature and automatically dial the pre-programmed telephone number. A complete system was developed in this work to measure the temperature and make emergency calls. It was tested and found to work properly. This work is of a major benefit because of the technique of using a dialing system as an alarm of temperature. It is a remote monitoring and alarming system. It can be concluded that this system could be used in many applications where the need of remote sensors and alarming system is needed. Some changes and improvements can be added as required by each application.